URGENSI PENGUATAN KARAKTER MAHASISWA CALON GURU DALAM EKOSISTEM PEMBELAJARAN DIGITAL - Cep Miftah Khoerudin; Titi Alawiyah (UNTIRTA CIVIC EDUCATION JOURNAL, 2026)
The rapid development of digital technology has fundamentally transformed educational systems, shifting learning from conventional approaches to digital-based environments. This transformation not only changes instructional practices but also influences the values, attitudes, and character of prospective teachers. This study aims to examine the urgency of strengthening character among pre-service teachers within a digital learning ecosystem, particularly in micro teaching courses. A qualitative approach with a case study design was employed to explore students’ character manifestations, challenges in digital learning, and strategies for character reinforcement. Data were collected through participatory observation, interviews, documentation, and reflective writing, and analyzed using interactive techniques involving data reduction, display, and conclusion drawing. The findings reveal that students demonstrate relatively good responsibility, discipline, and initial awareness of digital ethics; however, these characteristics are not yet fully internalized. Issues such as superficial use of digital resources, limited academic integrity, and suboptimal communication ethics indicate a gap between digital competence and character development. The study concludes that character strengthening is highly urgent and must be systematically integrated into digital learning processes. Micro teaching plays a strategic role as a reflective and authentic learning space to foster professional identity, ensuring that future teachers are not only technologically competent but also ethically grounded and responsible in digital environments.